2004
DOI: 10.1021/la049932x
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Albumin Self-Assembly on Weak Polyelectrolyte Multilayer Films Structurally Modified by pH Changes

Abstract: Adsorption of proteins onto film surfaces built up layer by layer from oppositely charged polyelectrolytes is a complex phenomenon, governed by electrostatic forces, hydrogen bonds, and hydrophobic interactions. The amounts of the interacting charges, however, both in polyelectrolytes and in proteins adsorbed on such films are a function of the pH of the solution. In addition, the number and the accessibility of free charges in proteins depend on the secondary structure of the protein. The subtle interplay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
105
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 39 publications
(60 reference statements)
9
105
0
1
Order By: Relevance
“…In the literature, [14][15][16] several studies of protein adsorption on previously formed polyelectrolyte multilayers could be found. Müller and coworkers [14] examined the sorption of HSA on poly(ethyleneimine)/poly(acrylic acid) multilayers using ATR FTIR spectroscopy, while Gergelly et al [15] analysed adsorption of the same protein on poly(L-lysine)/ poly(glutamic acid) multilayer by Optical Waveguide LightMode Spectroscopy (OWLS) and AFM. The secondary structure of lysozyme and bovine serum albumin (BSA) adsorbed onto PAH/PSS multilayers was investigated by Schaaf and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, [14][15][16] several studies of protein adsorption on previously formed polyelectrolyte multilayers could be found. Müller and coworkers [14] examined the sorption of HSA on poly(ethyleneimine)/poly(acrylic acid) multilayers using ATR FTIR spectroscopy, while Gergelly et al [15] analysed adsorption of the same protein on poly(L-lysine)/ poly(glutamic acid) multilayer by Optical Waveguide LightMode Spectroscopy (OWLS) and AFM. The secondary structure of lysozyme and bovine serum albumin (BSA) adsorbed onto PAH/PSS multilayers was investigated by Schaaf and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work has demonstrated that the interactions of proteins with polymeric surfaces strongly depend on the charge states of both a protein and a surface. [35,36] Accordingly, the highly polycationic rSilC molecules (pI ¼ 11.8) are expected to adsorb and remain strongly tethered to the negatively charged PSS surface (pK a ¼ 1) [37] at acidic and neutral pH. The presence of tethered rSilC was confirmed by in-situ attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy, which revealed two characteristic bands in the amide I (1600-1700 cm…”
mentioning
confidence: 99%
“…These films can be functionalised with widely varying features, ranging from antifungal activity (Etienne et al, 2005) to antiinflammatory properties (Schultz et al, 2005) to electro-optical devices (Eckle and Decher, 2001). By varying the electrolytes and/or the build-up conditions, the properties of the films -such as thickness (Shiratori and Rubner, 2000), cell adhesion , and protein adsorption (Gergely et al, 2004) -can be largely modified (Figure 3, panels a and b). The build-up of the polyelectrolyte film began with poly(ethyleneimine) (PEI).…”
Section: Artificial Membranesmentioning
confidence: 99%
“…It seems that the forces which keep the DPPC bilayer together, in order to optimise the bilayer structure, can compress the extruding parts of the PGA/PLL films (Pilbat et al, 2007). Depending on the components used, polyelectrolyte films may exhibit linear or exponential growth regimes Gergely et al, 2004). Exponential growth requires the free diffusion of at least one of the film components in the interior of the film .…”
Section: Artificial Membranesmentioning
confidence: 99%